Studi Kepustakaan Kejadian Toxoplasmosis pada Ternak Kambing di Indonesia - Maria Trifonia Kadha Geo; Diana A. Wuri M.Si; Novalino H.G Kallau M.Si (Jurnal Veteriner Nusantara, 2022)
Toxoplasmosis is a parasitic disease caused by Toxoplasma gondii (T. gondii). T. gondii infection occurs worldwide and is one of the many zoonotic diseases, namely diseases that can naturally be transmitted from animals to humans. The definitive host for toxoplasmosis is cats, while goats, sheep and humans are intermediate hosts. The incidence of toxoplasmosis in goats is widespread in Indonesia. Data regarding the incidence of toxoplasmosis in goats for all of Indonesia is incomplete and has not been updated, this is because new research has been carried out in certain areas, not all regions in Indonesia have conducted examinations or research on the incidence of toxoplasmosis in goats. Toxoplasmosis in goats in Indonesia is widespread in several provinces, such as Central Java, East Java, Yogyakarta, Bali, Aceh, Lampung and South Sulawesi. The prevalence of toxoplasmosis in these areas shows a different and quite high rate. The prevalence of toxoplasmosis in several provinces in Indonesia ranges from 15% to 100%. The risk factors that support the incidence of toxopasmosis in goats are cat population, maintenance and feed management, environment and age and sex.Toxoplasmosis, Goats, Prevalence, Risk factors, Indonesia.